Toward sustainable cities: Monitoring thermal environment for buildings and pedestrian space using drone-captured 3D thermal imaging - Alkaabi, Khaula; Senghore, Salieu; Rhman El Fawair, Abdel (Frontiers in Built Environment, 2023)
UAE's average temperature has risen in recent years and is expected to rise more in the next 40 years, creating a massive heat island agglomeration. Therefore, the demand for energy saving and diversified personal thermal management requires innovative solutions combining advanced building materials and structural designs to provide personal thermal comfort during indoor and outdoor activities. However, due to the complexities of structural designs and their associated materials, analytical and numerical strategies are for revealing real-world scenarios are limited. Therefore, full-scale experiments are required for exploring and demonstrating dynamic scenarios under thermal stress. This study explored the feasibility of using drone along with various thermal image analysis software that enables thermal photogrammetric mapping for monitoring and classification of heat rates based on building components surveyed across the UAEU campus. Several thermal images of two separate buildings incorporating different materials along with parking and pedestrian areas involving shaded, unshaded, and green zones are obtained and analyzed through a detailed statistical analysis. Results explore the temperature evolution process and its dependence on building materials and structural designs, offering first-hand research data based on building components for UAE climate, setting the path for additional research in the era of sustainability and urban development.